The early globalization of the cultural heritage of the Americas: merchant Hermann Strebel and his study of the Lahmann Collection from Costa Rica - Rojas Garro, Myrna (2026)
The present contribution is dedicated to an archaeological text written in German language that until now has been translated into Spanish despite the passage of 142 years after its original publication. Its author represents not only one of the protagonists of the beginnings of systematic archaeology in Europe, but also in Central America and Mexico. Through the study of the Lahmann Collection, the text is dedicated to the first great collection of archeological objects that left Costa Rica. Initiating a long tradition of looting Cultural Heritage at a historical moment when there was no legislation, nor awareness of its importance, this collection represents an outstanding example of the need and urgency to recover lost memories. In addition, the quality and quantity of the artifacts analyzed should motivate contemporary archaeologist to rescue at least the associated textual and graphic documentation, so that in some way their data can be integrated into the stratigraphic and contextual investigations of the present.